MAPK-driven epithelial cell plasticity drives colorectal cancer therapeutic resistance - Mark White; Megan L. Mills; Laura M. Millett; Kathryn Gilroy; Yourae Hong; Lucas B. Zeiger; Rosalin J. Simpson; Shania M. Corry; Amelia Ligeza; Tamsin R. M. Lannagan; Susanti Susanti; Rachel A. Ridgway; et al. (Nature, 2026)
Abstract The colorectal epithelium is rapidly renewing, with remarkable capacity to regenerate following injury. In colorectal cancer (CRC), this regenerative capacity can be co-opted to drive epithelial plasticity. Although oncogenic MAPK signalling in CRC is common, with frequent mutations of both KRAS (40–50%) and BRAF (10%) 1 , inhibition of this pathway typically drives resistance clinically. Here, given the development of KRAS inhibitors and licensing of BRAF inhibitor combinations 2–4 , we have interrogated key mechanisms of resistance to these agents in advanced preclinical CRC models. We show that oncogenic MAPK signalling induces epithelial-state changes in vivo, driving adoption of a regenerative/revival stem-like population, whereas inhibition leads to rapid transcriptional remodelling of both Kras -mutant and Braf- mutant tumours, favouring a WNT-associated, canonical stem phenotype. This drives acute therapeutic resistance in Kras -driven and delayed resistance in Braf -driven models. Where plasticity is restrained, such as in early metastatic disease, or through targeting ligand-dependent WNT pathway Rnf43 mutations, marked therapeutic responses are observed. This explains the super response to BRAF + EGFR-targeted therapies previously observed in a BRAF–RNF43 co-mutant patient population, highlighting the criticality of cellular plasticity in therapeutic response. Together, our data provide clear insight into the mechanisms underpinning resistance to MAPK-targeted therapies in CRC. Moreover, strategies that aim to corral stem cell fate, restrict epithelial plasticity or intervene when tumours lack heterogeneity may improve therapeutic efficacy of these agents.